2017
DOI: 10.1177/0969733017712083
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between moral distress and ethical climate with job satisfaction in nurses

Abstract: Identifying ethical stressors in the workplace and giving proper feedback to the authorities to eliminate these factors and improve the ethical climate in these workplaces can help enhance job satisfaction in nurses and lead to higher quality care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
72
1
10

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(122 citation statements)
references
References 42 publications
9
72
1
10
Order By: Relevance
“…In the present study, the highest score is for the domain of relationship with managers, which is consistent with the results of the study of Asgari [ 35 ]. This finding stresses the importance of the role of managers in improving the ethical climate in organizations.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, the highest score is for the domain of relationship with managers, which is consistent with the results of the study of Asgari [ 35 ]. This finding stresses the importance of the role of managers in improving the ethical climate in organizations.…”
Section: Discussionsupporting
confidence: 93%
“…Another finding of the present study is the existence of a significant positive relationship between ethical climate and the indexes of nurses’ professional quality of life—compared to the other indexes, compassion satisfaction has a stronger relationship with ethical climate. The ethical climate reflects the personnel’s perception of the performance of their organization about decision-making and feedback [ 35 ]. In the present study, the status of the ethical climate was found to be average.…”
Section: Discussionmentioning
confidence: 99%
“…From studies using the MDS, MDS-R, or modifications of the MDS-R, ICU nurses experienced varying levels of moral distress, ranging from relatively low levels 32,34 to moderate 8,28 and high 29 levels. In parallel, studies of non-ICU nurses also reported varying levels, from low 31 to moderate 27 to high.…”
Section: Resultsmentioning
confidence: 99%
“…The emotional distress experienced by critical care nurses who care for dying patients remains poorly understood. Current literature focuses primarily on posttraumatic stress disorder symptoms and moral distress (5,(15)(16)(17)(18)(19)(20)(21). Here we examine nurses' self-reported emotional distress in caring for ICU patients in the patients' last week of life.…”
mentioning
confidence: 99%